Scenario of Work-Life Balance Among Employed Women in the Public Sector of Lalitpur District - Shahi, Hari Bhakta (Innovative Research Journal, 2023)
The Constitution of Nepal 2072 emphasizes women's employment particularly the quota system developed for women in the public sector. This is an opportunity for women on one side and on the other side they are facing pressure due to their double roles and function. Nepali society is adopting both traditional and modern theories. Traditionally women are engaged in household activities. But in modern society, women are engaged in various activities including office work out of their house. Nepali-employed women are suffering from dual roles and functions. Nepali women especially those engaged in public sector offices are busy in various service delivery offices. In the public sector of Nepal, Nepali-employed women are highly criticized due to their low performance. This is due to their dual role. Women are responsible for their household activities such as; cooking, lodging, care of children as well as senior citizens, cleaning, guest management, clothing, waste management, and so on. Due to these household chores, women are busy in the house. On the other hand, public sector employed women have to be involved in various activities in the office such as service delivery, meeting, day-to-day activities, training, and so on. Therefore, public sector-employed women are facing a high level of pressure and cannot work well in the office. Developed countries run their administrative activities by the system. Public sector-employed women are successful in these countries. Women who are busy in the public sector manage their children, some senior citizens in the care center. Similarly cleaning, and washing, are also managed by the private sector in developed countries. So, urban areas like Lalitpur, Kathmandu, and Biratnagar should follow foreign trends. The government of Nepal should also develop a system for public sector-employed women.